Motivation for Social Responsibility in Nuclear Power Plants (Journal of Universal Excellence, 2026)
Research Question (RQ): What motivates owners and operators of Nuclear Power Plants (NPPs) for socially responsible acts?Purpose: This research identifies the dominant motives for the social responsibility of owners and operators of NPPs.Method: After reviewing the relevant literature of the presented field of interest, we included the owners and operators of the NPPs in the research. They are members of the international organization World Association of Nuclear Operators (WANO), with a regional centre in Paris. As an instrument for obtaining the information, we used a developed questionnaire. For the evaluation of data, we used descriptive and frequency statistics, the Mann-Whitney test, Wilcoxon rank test, and Kruskal-Wallis test.Results: 43 representatives of operators and 3 owners of NPPs cooperated in the research. Motivational factors for socially responsible activities include intrinsic elements, in particular personal ethical and moral values and personal satisfaction. We did not find statistically significant differences in motivation between operators and owners. In most cases, these differences were not statistically significant, considering their function in the organization. Operators and owners of NPPs demonstrated a high willingness to meet the expectations of a wider society.Organization: The results help NPPs in establishing and consolidating the positive image of a socially responsible organization.Society: The wider society is aware that the owners and operators of the NPPs obviously demonstrate that they want to act socially responsibly. It affects the acceptability of the NPPs and the quality of life of individuals and different groups in modern society and the environment in which nuclear facilities are located.Originality: This research is the first one as known to the author that is aimed at studying the motivational factors of the owners and operators of the NPPs for socially responsible actions. The results are directly applicable and relevant in Slovenia and other countries with NPPs. They contribute to a better understanding of the interactions between society and nuclear facilities.Limitations / further research: The responsiveness of the owners of the NPPs was not as good as the responsiveness of the operators; therefore, the sample is less representative of the owners. This research also focused on the inspirations that influence the motivation for establishing partnership relations with the NPPs, of the external stakeholders of the NPPs (local communities, political public, NGOs, journalists and others).
Keywords: intrinsic and extrinsic motivational factors; coexistence with the nuclear power plant; social responsibility